Studi pustaka dinamika sosialisasi pada individu ekstrovert dan introvert - Qolbi, Delima Dawaul (Maliki Interdisciplinary Journal, 2024)
Nowadays, many people label personality with two types: extroverts and introverts. Extroversion and Introversion are two personality types that influence the way individuals interact and communicate with their social environment. Through an analysis of existing literature, this study explores the socialization characteristics of these two personality types, including social activity preferences, interaction patterns, and the psychological impact of socialization. Extroverted individuals tend to be more active in participating in social activities and derive energy from interactions with others, while introverted individuals prefer fewer but deeper interactions, and often need time alone to recharge. This research discusses the implications of such socialization dynamics in the context of mental health. It also provides greater insight into how personality types can influence individuals’ social experiences and emphasizes the importance of tailored approaches in supporting different socialization needs.